Influence of emotional education in the teaching-learning process - Frisa María Antonieta Aliaga Guevara; Rocío Belú Ortecho Aguirre; José Felipe Villanueva Butrón (Revista de Ciencias Sociales, 2025)
Human behavior is conditioned by the experience of one’s own life. Science has tried to study and predict behaviors in order to improve the development of human capacities and skills. Thus, the theory of the economy of caresses suggests that the lack of affection can generate problems in the development of the person, such as existential emptiness, low self-esteem, lack of confidence and difficulties in learning. By applying this theory to emotional education, it is proposed that emotions, as an essential driving force of the human being, should be an integral part of the educational process, since they significantly influence the emotional development, learning and growth of students. Therefore, the objective of this article is to determine the influence of emotional education in the teaching-learning process, based on the hypothesis that its implementation is essential to guarantee adequate development in said process. As a result, the work of the educator will be necessary, who in the 21st century must not only educate in ideas but also promote emotional responsibility. It is concluded that these approaches highlight the fundamental role of emotional education as a cross-cutting axis in comprehensive training.